Pemahaman Pernikahan Kudus Suku Dawan Ditinjau Dari Kejadian 1:27-28 - Sjanette Eveline; Anita Mauboy (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
With the increasing number of Timorese Dawan who are married they are not in accordance with what is right before God today. Certainly making the servants of God must pay special attention and focus looking for various ways how to prevent and overcome the situation. And this is also very important to be studied. Why? Because of the habits that practiced by the Timor Dawan tribe rampant until now and this has a negative impact on the generation of teenagers and youth of the Dawan Timor tribe. And keep in mind that habits like this are also something evil in God's eyes. Therefore, as people who believe in God need to pay attention to this problem and find ways to prevent and improve this habit because this is something that is wrong and that is not pleasing before God. With this, the author is burdened to examine this problem with qualitative method. So that if you wish through this research, the people of Timor Dawan can turn those bad habits into habits that are in accordance with Genesis 1: 27-28. And this also needs to be applied by God's servants especially for God's servants who come from the Eastern Dawan tribe so that young people can see and apply their marriage properly and correctly before God and avoid bad associations that commit adultery before being blessed in the church.